STRUCTURAL MODELS OF ANATOMICAL TERMS OF THE LATIN LANGUAGE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The article is devoted to a systematic consideration of units of Latin anatomical terminology. The purpose of the work is to identify all structural models of Latin terms functioning in modern medical science and their typological representation. Scientific novelty is due to the systematic approach to the description of anatomical terms of the Latin language, as well as the fact that for the first time the structural typology of Latin anatomical terminological units and their quantitative relationship are established.